Self-repairing electrochromic device, preparation method and application thereof

CN123010294APending Publication Date: 2026-10-30ZHEJIANG JINGSHENG FILM TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611507387.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种自修复型电致变色器件及其制备方法与应用,实现全膜层、全方位的常温自修复,从根本上解决损伤后性能不可逆衰减的问题

Benefits of technology

[0094](1)本发明提供的自修复型电致变色器件,采用自修复电致变色层、自修复界面过渡层、自修复离子导体层和自修复离子存储层的复合设计,实现器件力学损伤、光学性能、电学性能的全方位常温自修复,使用寿命大幅延长,从根本上解决损伤后性能不可逆衰减的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a self-repairing electrochromic device and a preparation method and application thereof. The self-repairing electrochromic device comprises a substrate and a first transparent conductive layer, a self-repairing electrochromic layer, a self-repairing interface transition layer, a self-repairing ion conductor layer, a self-repairing ion storage layer and a second transparent conductive layer which are sequentially stacked on the substrate. The composite design of the self-repairing electrochromic layer, the self-repairing interface transition layer, the self-repairing ion conductor layer and the self-repairing ion storage layer realizes all-around normal-temperature self-repairing of mechanical damage, optical performance and electrical performance of the device, and fundamentally solves the problem of irreversible performance attenuation after damage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochromic technology, and relates to a self-healing electrochromic device, its preparation method and application. Background Technology

[0002] Electrochromic rearview mirrors, as intelligent optical components for automobiles, operate under complex conditions of high vibration, multiple impacts, and strong wear. Impacts from gravel during driving, wipers, physical friction during car washes, and thermal expansion and contraction caused by temperature changes can all easily lead to micro-cracks, micro-scratches, and micro-separation of the film layer.

[0003] Currently, the films in all-solid-state electrochromic rearview mirrors generally employ static covalent cross-linking or physical blending structures, lacking dynamic rearrangement capabilities in their molecular chains. Once damaged, ion transport channels, film structure, and interfacial bonding will suffer irreversible damage, manifesting as prolonged color-changing response time, decreased optical contrast, and increased leakage current; in severe cases, the device may fail completely. Industry data shows that over 60% of existing electrochromic rearview mirror failures are due to physical damage, significantly shortening product lifespan and reducing user experience.

[0004] Currently, industry solutions mainly focus on passive protection, such as increasing the thickness of the SiO2 protective layer, using scratch-resistant coatings, and optimizing the packaging structure. No active self-healing technology has yet emerged. Self-healing technology, however, is already maturely applied in coatings, rubber, and electronic packaging. Combining self-healing technology with electrochromic devices to achieve active repair after damage has become the core development direction for the high-end and long-life development of electrochromic rearview mirrors.

[0005] In conclusion, there is an urgent need to develop an electrochromic device with self-healing capabilities to meet the long-term usage requirements in harsh automotive environments. Summary of the Invention

[0006] The purpose of this invention is to provide a self-healing electrochromic device, its preparation method and application, to achieve full-film, all-round room temperature self-healing, fundamentally solving the problem of irreversible performance degradation after damage.

[0007] To achieve this objective, the present invention adopts the following technical solution:

[0008] In a first aspect, the present invention provides a self-healing electrochromic device, the self-healing electrochromic device comprising a substrate and a first transparent conductive layer, a self-healing electrochromic layer, a self-healing interface transition layer, a self-healing ion conductor layer, a self-healing ion storage layer and a second transparent conductive layer sequentially stacked on the substrate.

[0009] The self-healing electrochromic device provided by this invention adopts a composite design of a self-healing electrochromic layer, a self-healing interface transition layer, a self-healing ion conductor layer and a self-healing ion storage layer, to achieve all-round room temperature self-repair of mechanical damage, optical performance and electrical performance of the device, fundamentally solving the problem of irreversible performance degradation after damage.

[0010] It should be noted that the use of a self-healing electrochromic layer and a self-healing ion storage layer can achieve molecular chain cross-linking healing of microcracks, restore ion transport channels and electrochromic active sites; the use of a self-healing interface transition layer can repair interlayer microseparation, ensure interlayer bonding and ion transport continuity, and eliminate interface scattering; the use of a self-healing ion conductor layer can restore the film structure and ion transport performance, while isolating water vapor and oxygen.

[0011] Preferably, the substrate comprises glass.

[0012] In this invention, the substrate is pretreated before use to ensure that the surface roughness Ra is ≤2nm, thus providing an ultra-clean substrate for subsequent film preparation.

[0013] Preferably, the light transmittance of the substrate is ≥92%, for example, it can be 92.2%, 92.5%, 92.8%, 93%, 93.2%, 93.5%, 93.8%, 94%, 94.2%, 94.5%, 94.8%, or 95%, etc.; the haze is ≤0.1%, for example, it can be 0.09%, 0.08%, 0.07%, 0.06%, 0.05%, 0.04%, or 0.02%, etc.; the thickness is 2mm-3mm, for example, it can be 2.1mm, 2.2mm, 2.3mm, 2.4mm, 2.5mm, 2.6mm, 2.7mm, 2.8mm, or 2.9mm, etc.

[0014] Preferably, the light transmittance of both the first transparent conductive layer and the second transparent conductive layer is ≥91%, for example, it can be 91.2%, 91.5%, 91.8%, 92%, 92.2%, 92.5%, 92.8%, 93%, 93.2%, 93.5%, 93.8% or 94%, etc.; the haze is ≤0.1%, for example, it can be 0.09%, 0.08%, 0.07%, 0.06%, 0.05%, 0.04% or 0.02%, etc.; the thickness is 100nm-200nm, for example, it can be 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm or 190nm, etc.

[0015] Preferably, both the first transparent conductive layer and the second transparent conductive layer are transparent conductive layers with gradient doping of metal oxides, wherein the content of doped metal oxides decreases from the center of the transparent conductive layer to both sides.

[0016] In this invention, a metal oxide gradient doped transparent conductive layer is used, which can balance the resistance of the conductive layer, alleviate thermal stress, reduce optical scattering, and optimize the interface bonding effect with adjacent functional layers. The transparent conductive layer includes an ITO (indium tin oxide) layer, an FTO (fluorine-doped tin oxide) layer, or an AZO (aluminum-doped zinc oxide) layer.

[0017] Preferably, the metal oxide doped in the transparent conductive layer includes any one or a combination of at least two of ZnO, Al2O3, Ga2O3, In2O3, or SnO2.

[0018] Preferably, the doped metal content at the center of the transparent conductive layer is 2%-3%, for example, it can be 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8% or 2.9%; the doped metal content at both sides is 0%-0.05%, for example, it can be 0.01%, 0.02%, 0.03% or 0.04%.

[0019] Preferably, the thickness of the self-healing electrochromic layer is 300nm-500nm, for example, it can be 320nm, 340nm, 350nm, 360nm, 380nm, 400nm, 420nm, 440nm, 450nm, 460nm or 480nm, etc.

[0020] Preferably, the raw materials for preparing the self-healing electrochromic layer include a dynamically covalent polymer and a first metal oxide sol.

[0021] It should be noted that when microcracks are generated in the electrochromic layer modified with dynamic covalent bonds, the dynamic covalent bonds at the cracks break and rearrange. The molecular chains achieve cross-linking healing through the reversible combination of hydrogen bonds and dynamic covalent bonds, restoring the ion transport channels and the membrane structure. This enables the electrochromic layer to self-repair at room temperature, solving the industry problem of inorganic membranes lacking self-repair capabilities.

[0022] Preferably, the dynamically covalent polymer includes polymers containing acylhydrazone bonds and / or polymers containing disulfide bonds.

[0023] Preferably, the polymer containing acylhydrazone bonds is a condensation polymer of acylhydrazine compounds and dialdehydes.

[0024] In this invention, the acylhydrazine compounds include any one or a combination of at least two of adipic hydrazine, oxalate dihydrazine, malonate dihydrazine, or terephthalate dihydrazine; the dialdehydes include any one or a combination of at least two of terephthalaldehyde, glyoxal, isophthalaldehyde, or biphenyl dialdehyde.

[0025] Preferably, the polymer containing disulfide bonds is a condensation polymer of dithiocarboxylic acid compounds and dithiol compounds.

[0026] In this invention, the dithiocarboxylic acid compounds include dibenzoic acid disulfide and / or diphenyl dithiocarboxylic acid; the dithiol compounds include diethanol disulfide and / or 1,9-nonanedithiol.

[0027] In this invention, there are no particular restrictions on the type of polymerization reaction and reaction parameters for preparing polymers containing acylhydrazone bonds and polymers containing disulfide bonds, as long as the polymer obtained from the reaction contains acylhydrazone bonds or disulfide bonds.

[0028] Preferably, the first metal oxide sol includes WO3 sol and / or WO3-TiO2 sol.

[0029] In this invention, the mass ratio of tungsten source to titanium source in the WO3-TiO2 sol is (92-98):(2-8), for example, it can be 93:7, 94:6, 95:5, 96:4, or 97:3, etc. The tungsten source includes ethyl tungstate; the titanium source includes tetrabutyl titanate.

[0030] In this invention, there are no particular restrictions on the preparation method of the first metal oxide sol; the conventional sol-gel method can be used.

[0031] Preferably, based on the mass of the first metal oxide sol being 100%, the mass percentage of the dynamic covalent polymer is 5%-8%, for example, it can be 5.2%, 5.5%, 5.6%, 5.8%, 6%, 6.2%, 6.5%, 6.6%, 6.8%, 7%, 7.2%, 7.5%, 7.6% or 7.8%, etc.

[0032] Preferably, the thickness of the self-healing interface transition layer is 20nm-50nm, for example, it can be 22nm, 25nm, 26nm, 28nm, 30nm, 32nm, 35nm, 36nm, 38nm, 40nm, 42nm, 45nm, 46nm or 48nm, etc.

[0033] Preferably, the raw materials for preparing the self-healing interface transition layer include dynamic hydrogen-bonded organosiloxanes and...

[0034] It should be noted that when interfacial microseparation occurs, dynamic hydrogen bonds can recombine, repairing interfacial gaps, ensuring the continuity of interlayer bonding and ion transport, and eliminating interfacial scattering.

[0035] Preferably, the dynamic hydrogen-bonded organosiloxane comprises amino silicone oil and polyethylene glycol siloxane in a mass ratio of (2-5):1, such as 2.5:1, 3:1, 3.5:1, 4:1 or 4.5:1.

[0036] In this invention, amino and hydroxyl groups in the transition layer of the self-healing interface form dynamic hydrogen bonds.

[0037] In this invention, if the amount of amino silicone oil is too small, the self-healing efficiency of the interface transition layer decreases; if the amount of amino silicone oil is too large, the system compatibility decreases, the light transmittance of the self-healing interface transition layer decreases, and the haze increases.

[0038] Preferably, the thickness of the self-healing ion conductor layer is such that the light transmittance is ≥92%, for example, it can be 92.2%, 92.5%, 92.8%, 93%, 93.2%, 93.5%, 93.8%, 94%, 94.2%, 94.5%, 94.8%, or 95%; and the thickness is 5μm-15μm, for example, it can be 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, or 14μm.

[0039] Preferably, the self-healing ion conductor layer comprises the following components: core-shell self-healing microcapsules, modified siloxane, siloxane-modified polyethylene glycol, and lithium salt.

[0040] In this invention, when the ion conductor layer is damaged and microcracks or pores appear, the core-shell self-healing microcapsules rupture, releasing self-healing monomers. These monomers then polymerize with the silanol groups in the ion conductor layer, filling the cracks or pores and restoring the mechanical structure and ion transport channels of the film, while simultaneously isolating water vapor and oxygen. Modified siloxanes are used to ensure the high light transmittance of the self-healing ion conductor layer, and siloxane-modified polyethylene glycol is used for lithium-ion conductivity and reacts with the core-shell self-healing microcapsules.

[0041] Preferably, the mass ratio of the core-shell self-healing microcapsule, modified siloxane, siloxane-modified polyethylene glycol, and lithium salt is (3-5):(10-15):(30-40):(40-50), for example, it can be 3:10:30:40, 4:12:35:45, or 5:15:40:50, etc.

[0042] Preferably, the core-shell self-healing microcapsule includes a core and a shell, wherein the core includes a self-healing monomer and the shell includes SiO2.

[0043] It should be noted that the core-shell self-healing microcapsules use SiO2 as the shell and self-healing monomers as the core. They are fully compatible with the electrochromic system, dispersed in the ion conductor layer without optical scattering, and simultaneously achieve dual repair of mechanical damage and ion transport performance.

[0044] Preferably, the core-shell self-healing microcapsules are prepared by in-situ polymerization.

[0045] Preferably, the self-healing monomer comprises polyetheramine and / or epoxy acrylate.

[0046] Preferably, the thickness of the outer shell is 50nm-100nm, for example, it can be 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm or 95nm, etc.

[0047] Preferably, the core-shell self-healing microcapsules have a light transmittance ≥95%, such as 95.2%, 95.5%, 95.8%, 96%, 96.2%, 96.5%, 96.8%, 97%, 97.2%, 97.5%, 97.8%, or 98%; and an average particle size of 1μm-3μm, such as 1.2μm, 1.5μm, 1.6μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.6μm, or 2.8μm.

[0048] Preferably, the modified siloxane includes fluorosiloxanes and alkylsiloxanes.

[0049] In this invention, the alkylsiloxane includes any one or a combination of at least two of diethylsiloxane, methylphenylsiloxane, or octylsiloxane.

[0050] Preferably, the lithium salt comprises LiTFSI (lithium bis(trifluoromethanesulfonylimide)).

[0051] Preferably, the thickness of the self-healing ion storage layer is 200nm-400nm, for example, it can be 220nm, 250nm, 260nm, 280nm, 300nm, 320nm, 350nm, 360nm or 380nm, etc.

[0052] Preferably, the raw materials for preparing the self-healing ion storage layer include a dynamic covalent polymer and a second metal oxide sol.

[0053] It should be noted that when microcracks are generated in the ion storage layer using materials modified with dynamic covalent bonds, the dynamic covalent bonds at the cracks also break and rearrange. The molecular chains achieve cross-linking healing through the reversible combination of hydrogen bonds and dynamic covalent bonds, thus restoring the ion transport channels and the membrane structure.

[0054] Preferably, the second metal oxide sol includes NiO sol and / or NiO-TiO2 sol.

[0055] In this invention, the mass ratio of nickel source to titanium source in the NiO-TiO2 sol is (8-10):1, for example, it can be 8.2:1, 8.5:1, 8.6:1, 8.8:1, 9:1, 9.2:1, 9.5:1, 9.6:1, or 9.8:1, etc. The nickel source includes nickel nitrate.

[0056] In this invention, there are no particular restrictions on the preparation method of the second metal oxide sol; the conventional sol-gel method can be used.

[0057] Preferably, based on the mass of the second metal oxide sol as 100%, the mass percentage of the dynamic covalent polymer is 5%-8%, for example, it can be 5.2%, 5.5%, 5.6%, 5.8%, 6%, 6.2%, 6.5%, 6.6%, 6.8%, 7%, 7.2%, 7.5%, 7.6% or 7.8%, etc.

[0058] Preferably, the self-healing electrochromic device further includes: a self-healing protective layer and a self-healing encapsulation layer sequentially stacked on the second transparent conductive layer.

[0059] In this invention, devices with a self-healing protective layer and a self-healing encapsulation layer are subjected to comprehensive testing for damage resistance and self-healing. After automotive simulated vibration test (5~2000Hz, 100h) and sand impact test (particle size ≤2mm, speed 50km / h), the film layer showed no peeling or significant damage. Even if micro-damage occurs, it can quickly self-heal at room temperature without the need for external stimuli such as high temperature, ultraviolet light, or external electric field.

[0060] Preferably, the thickness of the self-healing protective layer is 80nm-120nm, for example, it can be 85nm, 90nm, 95nm, 100nm, 105nm, 110nm or 115nm, etc.; the surface hardness is ≥6H, for example, it can be 6H, 6.5H, 7H, 7.5H or 8H, etc.

[0061] Preferably, the raw materials for preparing the self-healing protective layer include wear-resistant materials and organosiloxanes in a mass ratio of (2-3):1, such as 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1 or 2.9:1, etc.

[0062] In this invention, a self-healing protective layer can be customized according to usage requirements. The dynamic bonds in the self-healing protective layer can achieve molecular chain rearrangement at room temperature to repair micro-scratches on the surface. At the same time, the wear-resistant material ensures the hardness of the protective layer, achieving a synergistic effect of scratch resistance and self-healing.

[0063] Preferably, the wear-resistant material includes SiO2 and / or TiO2.

[0064] Preferably, the organosiloxane includes SiOCH and / or PDMS (polydimethylsiloxane).

[0065] Preferably, the thickness of the self-healing encapsulation layer is 3μm-8μm, for example, it can be 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm or 7.5μm, etc.

[0066] Preferably, the raw material for preparing the self-healing encapsulation layer includes epoxy resin containing dynamic covalent bonds.

[0067] In this invention, epoxy resin containing dynamic covalent bonds is used for self-healing encapsulation. The epoxy resin forms crosslinks with the dynamic bonds of the film layer, repairing the micro gaps at the encapsulation edge, while isolating water vapor / oxygen, thereby improving the device's self-healing capability and environmental stability.

[0068] Preferably, the epoxy resin containing dynamic covalent bonds includes epoxy resins containing acylhydrazone bonds and / or epoxy resins containing disulfide bonds.

[0069] In this invention, the preparation method of epoxy resin containing acylhydrazone bonds can be carried out with reference to the method provided in Example 1 of CN120040719A; the preparation method of epoxy resin containing disulfide bonds can be carried out with reference to the method provided in Example 1 of CN119081067A.

[0070] In this invention, the selected self-healing materials are fully compatible with functional layers such as the electrochromic layer and the ion conductor layer, without any chemical side reactions. XPS and SEM tests show that the interfacial bonding between the film layers is tight, with no gaps or phase formation, and the dynamic bonding system is stable over a wide temperature range (-40℃ to 85℃).

[0071] Preferably, the haze of the self-healing electrochromic device is ≤0.5%, for example, it can be 0.48%, 0.46%, 0.45%, 0.42%, 0.4%, 0.35%, 0.3%, 0.25%, 0.2%, or 0.15%, etc.; the light transmittance is ≥92%, for example, it can be 92.2%, 92.5%, 92.8%, 93%, 93.2%, 93.5%, 93.8%, 94%, 94.2%, 94.5%, 94.8%, or 95%, etc.; the color change... Color response time ≤ 3s, for example, it can be 2.8s, 2.5s, 2.2s, 2s, 1.8s, 1.5s, 1.2s or 1s, etc.; fading response time ≤ 3s, for example, it can be 2.8s, 2.5s, 2.2s, 2s, 1.8s, 1.5s, 1.2s or 1s, etc.; cycle life ≥ 15,000 times, for example, it can be 15,200 times, 15,500 times, 15,800 times, 16,000 times, 16,500 times, 17,000 times or 18,000 times, etc.

[0072] Preferably, the self-healing electrochromic device has a self-healing rate of ≥85% when the crack width is ≤5μm, for example, it can be 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96% or 97%, etc.

[0073] In this invention, the haze refers to the haze in the transparent state.

[0074] It should be noted that by constructing a triple self-healing system consisting of dynamic covalent bonds, dynamic hydrogen bonds, and core-shell self-healing microcapsules, self-healing can be achieved at room temperature without the need for external stimuli such as high temperature, ultraviolet light, or applied electric fields. Through the synergistic effect of the triple self-healing system, mechanical damage such as microcracks, scratches, and interface separation is first repaired, followed by self-healing of the structure and ion transport channels, thereby restoring optical and electrical properties. Under optimal conditions, the electrochromic properties, optical properties, and mechanical properties of the repaired device can all be restored to more than 95% of their initial state.

[0075] In a second aspect, the present invention provides a method for preparing a self-healing electrochromic device as described in the first aspect, the method comprising:

[0076] A first transparent conductive layer, a self-healing electrochromic layer, a self-healing interface transition layer, a self-healing ion conductor layer, a self-healing ion storage layer, and a second transparent conductive layer are sequentially prepared on a substrate.

[0077] Preferably, both the first transparent conductive layer and the second transparent conductive layer are prepared by magnetron sputtering.

[0078] Preferably, the self-healing electrochromic layer, the self-healing interface transition layer, the self-healing ion conductor layer, and the self-healing ion storage layer are all prepared by spin coating.

[0079] In this invention, the preparation method of the self-healing electrochromic layer and the self-healing ion storage layer includes: spin-coating the sol mixture of the layer onto the surface of the first transparent conductive layer, and then sequentially vacuum curing at a temperature of 70℃-90℃ for 0.5h-2h and annealing at a temperature of 110℃-130℃ for 20min-40min.

[0080] In this invention, the method for preparing the self-healing interface transition layer includes: spin-coating a dynamic hydrogen-bonded organosiloxane onto the surface of the self-healing electrochromic layer, and then vacuum curing it at a temperature of 50℃-70℃ for 20min-40min.

[0081] In this invention, the preparation method of the self-healing ion conductor layer includes: dissolving each component in a mixed solvent, spin-coating it onto the surface of the self-healing interface transition layer, and then vacuum curing it at a temperature of 70℃-90℃ for 1h-3h.

[0082] Preferably, the preparation method further includes: preparing a self-healing protective layer on the second transparent conductive layer, annealing it, and then preparing a self-healing encapsulation layer on the self-healing protective layer.

[0083] Preferably, the self-healing protective layer is prepared by electron beam evaporation.

[0084] The preparation method provided by this invention is compatible with existing equipment for mass production of devices, such as magnetron sputtering, spin coating, and evaporation, without the need for additional dedicated equipment, and the cost is controllable.

[0085] Preferably, the annealing temperature is 80℃-120℃, for example, it can be 85℃, 90℃, 95℃, 100℃, 105℃, 110℃ or 115℃, etc.; the time is 40min-80min, for example, it can be 45min, 50min, 55min, 60min, 65min, 70min or 75min, etc.

[0086] In this invention, the self-healing electrochromic device is annealed to enhance the bonding force between the film layers, resulting in a bonding force >5MPa, while also making the dynamic bonding system more stable.

[0087] Preferably, the self-healing encapsulation layer is prepared by a scraping coating method.

[0088] In this invention, the method for preparing the self-healing encapsulation layer includes: applying the mixture to the surface of the self-healing protective layer, and then vacuum curing it at a temperature of 80℃-100℃ for 40min-60min.

[0089] In this invention, there are no particular restrictions on the operation steps and parameters of magnetron sputtering, spin coating and electron beam evaporation, which can be set according to production needs.

[0090] Thirdly, the present invention provides an application of the self-healing electrochromic device as described in the first aspect, wherein the self-healing electrochromic device is used in automotive rearview mirrors, smart windows, or display devices.

[0091] When the self-healing electrochromic device provided by this invention is used in a car rearview mirror, it can achieve in-situ self-healing during the car's driving or parking process, resulting in an excellent user experience.

[0092] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0093] Compared with the prior art, the present invention has the following beneficial effects:

[0094] (1) The self-healing electrochromic device provided by the present invention adopts a composite design of self-healing electrochromic layer, self-healing interface transition layer, self-healing ion conductor layer and self-healing ion storage layer to realize all-round room temperature self-healing of mechanical damage, optical performance and electrical performance of the device, greatly extending the service life and fundamentally solving the problem of irreversible performance degradation after damage.

[0095] (2) The self-healing electrochromic device provided by the present invention can repair surface micro-scratches and external impact damage, as well as repair micro-cracks inside the film layer, micro-separation of interlayer interface and micro-gap of encapsulation by adding a self-healing protective layer and a self-healing encapsulation layer, thereby further improving the self-healing capability and stability of the device.

[0096] (3) The self-healing electrochromic device provided by the present invention has excellent optical performance and electrochromic performance, and achieves a balance between self-healing function and low haze and high light transmittance. Under preferred conditions, the haze is ≤0.5%, the light transmittance is ≥92%, the color change response time is ≤3s, the fading response time is ≤3s, the cycle life is ≥15000 times, and the self-healing rate is ≥85% under the crack width ≤5μm.

[0097] (4) The preparation method provided by the present invention is compatible with existing equipment for mass production of devices, such as magnetron sputtering, spin coating, and evaporation, without the need for additional special equipment, and the cost is controllable. Detailed Implementation

[0098] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0099] All materials used in the specific embodiments of this invention can be purchased commercially or prepared using conventional methods in the prior art. Unless otherwise specified, the materials used in this invention are as follows:

[0100] The polymer containing acylhydrazone bonds was prepared by the following method: 0.4 mol adipic hydrazide and 0.4 mol terephthalaldehyde were mixed, and 0.05 mol acetic acid was added to the mixture. The polymerization reaction was carried out at 40 °C for 10 h to obtain the polymer containing acylhydrazone bonds.

[0101] The polymer containing disulfide bonds was prepared by the following method: 0.5 mol of dibenzoic acid disulfide and 0.5 mol of diethanol disulfide were mixed, and 5 g of sulfuric acid with a mass concentration of 98% was added. The polymerization reaction was carried out at 80°C for 10 h to obtain the polymer containing disulfide bonds.

[0102] WO3 sol was prepared by the following method: ethyl tungstate was dissolved in a mixed solvent of ethanol and acetic acid (volume ratio of 4:1), and hydrochloric acid with a mass concentration of 3.5% was added to catalyze hydrolysis. The mixture was stirred at room temperature for 2 hours to obtain the WO3 sol.

[0103] WO3-TiO2 sol was prepared by the following method: ethyl tungstate and tetrabutyl titanate were dissolved in a mixed solvent of ethanol and acetic acid (volume ratio of 7:3) at a mass ratio of 95:5, and hydrochloric acid with a mass concentration of 3.5% was added to catalyze hydrolysis. The mixture was stirred at room temperature for 2 hours to obtain the WO3-TiO2 sol.

[0104] NiO sol was prepared by the following method: nickel nitrate was dissolved in a mixed solvent of ethanol and acetic acid (volume ratio 3:2), and hydrochloric acid with a mass concentration of 3.5% was added to catalyze hydrolysis. The mixture was stirred at room temperature for 2 hours to obtain the NiO sol.

[0105] NiO-TiO2 sol was prepared by the following method: nickel nitrate and tetrabutyl titanate were dissolved in a mixed solvent of ethanol and acetic acid (volume ratio of 6.5:3.5) at a mass ratio of 9:1, and hydrochloric acid with a mass concentration of 3.5% was added to catalyze hydrolysis. The mixture was stirred at room temperature for 2 hours to obtain the NiO-TiO2 sol.

[0106] The preparation method of the epoxy resin containing acylhydrazone bonds is as provided in Example 1 of CN120040719A.

[0107] The preparation method of the epoxy resin containing disulfide bonds is as provided in Example 1 of CN119081067A.

[0108] Amino silicone oil: purchased from Huangshan Qiangli Chemical Co., Ltd., brand name QL-2212;

[0109] Polyethylene glycol siloxane: purchased from Elkay Silicones, grade LK-7300;

[0110] Polyetheramine: purchased from Huntsman Chemicals, brand name JEFFAMINE D-2000;

[0111] Epoxy acrylate: purchased from Guangdong Boxin New Material Technology Co., Ltd., grade B-102;

[0112] Fluorosiloxane: Purchased from Hubei Kefule Materials Technology Co., Ltd., grade CF-FS08;

[0113] Diethylsiloxane: Purchased from Hubei Jusheng Technology Co., Ltd., brand name JS-DE01;

[0114] Siloxane-modified polyethylene glycol: purchased from Hubei Changfu Chemical Co., Ltd., brand name ChangFu® MPE32;

[0115] SiOCH: Purchased from Dow Corning, brand name Z-6030;

[0116] PDMS: Purchased from Dow Corning, brand name Z-6030.

[0117] The methods used in the specific embodiments of this invention are all conventional techniques in the field. The substrates are pretreated before use, and the pretreatment includes sequential ultrasonic cleaning with acetone for 20 min, ultrasonic cleaning with anhydrous ethanol for 20 min, ultrasonic cleaning with deionized water for 20 min, ozone cleaning for 10 min, drying at 100°C for 30 min, and finally drying with nitrogen gas.

[0118] Example 1

[0119] This embodiment provides a self-healing electrochromic device and its preparation method. The self-healing electrochromic device includes a substrate and a first transparent conductive layer, a self-healing electrochromic layer, a self-healing interface transition layer, a self-healing ion conductor layer, a self-healing ion storage layer, and a second transparent conductive layer sequentially stacked on the substrate.

[0120] The substrate includes glass with a light transmittance of 95%, a haze of 0.05%, and a thickness of 2.5 mm;

[0121] Both the first and second transparent conductive layers have a light transmittance of 94%, a haze of 0.05%, and a thickness of 160 nm. Both the first and second transparent conductive layers are ZnO-doped ITO layers, with the ZnO content decreasing from the center of the ITO layer to both sides. Specifically, the Zn content at the center of the ITO layer is 2%, and the Zn content at both sides is 0%.

[0122] The thickness of the self-healing electrochromic layer is 400 nm; the raw materials for preparing the self-healing electrochromic layer include a dynamic covalent polymer and a first metal oxide sol, wherein the dynamic covalent polymer is a polymer containing acylhydrazone bonds, and the first metal oxide sol is a WO3-TiO2 sol; based on the mass of the first metal oxide sol being 100%, the mass percentage of the dynamic covalent polymer is 7%;

[0123] The thickness of the self-healing interface transition layer is 35 nm; the raw materials for preparing the self-healing interface transition layer include dynamic hydrogen-bonded organosiloxane, which includes amino silicone oil and polyethylene glycol siloxane in a mass ratio of 3:1.

[0124] The self-healing ion conductor layer has a transmittance of 95% and a thickness of 12 μm. The self-healing ion conductor layer comprises core-shell self-healing microcapsules, modified siloxane, siloxane-modified polyethylene glycol, and lithium salt in a mass ratio of 4:12:35:45. The core-shell self-healing microcapsules consist of a core and a shell, with the core being polyetheramine and the shell being SiO2. The core-shell self-healing microcapsules are prepared by dissolving tetraethyl orthosilicate in anhydrous ethanol, then adding polyetheramine, adjusting the pH to 9.5, and performing in-situ polymerization for 6 hours at room temperature with stirring to obtain core-shell self-healing microcapsules with an average particle size of 2 μm, a shell thickness of 70 nm, and a transmittance of 97%. The modified siloxane is a fluorosiloxane; the lithium salt is LiTFSI.

[0125] The thickness of the self-healing ion storage layer is 300 nm; the raw materials for preparing the self-healing ion storage layer include a dynamic covalent polymer and a second metal oxide sol, wherein the dynamic covalent polymer is a polymer containing acylhydrazone bonds and the second metal oxide sol is a NiO-TiO2 sol; based on the mass of the second metal oxide sol being 100%, the mass percentage of the dynamic covalent polymer is 7%.

[0126] The preparation method includes: sequentially preparing a first transparent conductive layer, a self-healing electrochromic layer, a self-healing interface transition layer, a self-healing ion conductor layer, a self-healing ion storage layer, and a second transparent conductive layer on a substrate, and then performing annealing.

[0127] Both the first and second transparent conductive layers were prepared by magnetron sputtering. Gradient co-magnetron sputtering was performed at room temperature using an ITO ceramic target and a Zn target. The sputtering power of the ITO ceramic target was kept constant at 120W, while the sputtering power of the Zn target was gradually increased from 0 to 18W and then gradually decreased back to 0. The gases used in preparing the first transparent conductive layer included oxygen and argon, with an argon partial pressure of 0.5Pa and a total gas pressure of 0.8Pa.

[0128] The self-healing electrochromic layer is prepared by spin coating. Specifically, it includes: adding a dynamic covalent polymer to a first metal oxide sol, ultrasonically dispersing it for 30 min, spin coating the sol mixture on the surface of the first transparent conductive layer at a speed of 500 r / min for 10 s, and then continuing to spin coat it at a speed of 3000 r / min for 30 s. Subsequently, it is vacuum cured at 80°C for 1 h and annealed at 120°C for 30 min to form a self-healing electrochromic layer.

[0129] The self-healing interface transition layer is prepared by spin coating; specifically, it includes: spin coating a dynamic hydrogen-bonded organosiloxane on the surface of the self-healing electrochromic layer at a speed of 2000 r / min for 20 s, followed by vacuum curing at 60℃ for 30 min to form the self-healing interface transition layer.

[0130] The self-healing ion conductor layer is prepared by spin coating. Specifically, the process involves dissolving core-shell self-healing microcapsules, modified siloxane, siloxane-modified polyethylene glycol, and lithium salt in a mixed solvent of ethanol and water (volume ratio 7:3), spin coating the mixture onto the surface of the self-healing interface transition layer at a speed of 3000 r / min for 30 s, and then vacuum curing it at 80 °C for 2 h to form the self-healing ion conductor layer.

[0131] The self-healing ion storage layer is prepared by spin coating. Specifically, it includes: adding a dynamic covalent polymer to the second metal oxide sol, ultrasonically dispersing it for 30 min, spin coating the sol mixture on the surface of the self-healing ion conductor layer at a speed of 500 r / min for 10 s, and then continuing to spin coat it at a speed of 3000 r / min for 30 s. Subsequently, it is vacuum cured at 80 °C for 1 h and annealed at 120 °C for 30 min to form the self-healing ion storage layer.

[0132] The annealing temperature is 100℃ and the time is 60 minutes.

[0133] In this embodiment, a composite design of a self-healing electrochromic layer, a self-healing interface transition layer, a self-healing ion conductor layer, and a self-healing ion storage layer is adopted to achieve all-round room-temperature self-healing of the device's mechanical damage, optical performance, and electrical performance. Furthermore, based on the application scenario, a self-healing protective layer and / or a self-healing encapsulation layer can be flexibly superimposed to form a multi-level self-healing architecture, thereby significantly enhancing the device's damage resistance and self-healing performance.

[0134] Example 2

[0135] This embodiment provides a self-healing electrochromic device and its preparation method. Based on Embodiment 1, a self-healing protective layer and a self-healing encapsulation layer are added, namely:

[0136] A self-healing protective layer and a self-healing encapsulation layer are sequentially stacked on the second transparent conductive layer; the thickness of the self-healing protective layer is 100 nm and the surface hardness is 6H; the raw materials for preparing the self-healing protective layer include a wear-resistant material and an organosiloxane in a mass ratio of 7:3, wherein the wear-resistant material is SiO2 and the organosiloxane is SiOCH.

[0137] The thickness of the self-healing encapsulation layer is 5 μm; the raw materials for preparing the self-healing encapsulation include epoxy resin containing dynamic covalent bonds, and the epoxy resin containing dynamic covalent bonds is epoxy resin containing acylhydrazone bonds.

[0138] The preparation method includes: sequentially preparing a first transparent conductive layer, a self-healing electrochromic layer, a self-healing interface transition layer, a self-healing ion conductor layer, a self-healing ion storage layer, a second transparent conductive layer, and a self-healing protective layer on a substrate, performing annealing, and then preparing a self-healing encapsulation layer on the self-healing protective layer.

[0139] The self-healing protective layer was prepared using electron beam evaporation; under a vacuum degree of 1×10⁻⁶. -4 SiO2 and SiOCH were co-deposited at a rate of 0.2 nm / s under Pa conditions.

[0140] The self-healing encapsulation layer is prepared by a scraping method; specifically, it includes: using anhydrous ethanol to adjust the epoxy resin containing acylhydrazone bonds to a solid content of 45wt%, scraping it onto the surface of the self-healing protective layer, and then vacuum curing it at a temperature of 90℃ for 50min.

[0141] The fabrication process used for the other layers in the self-healing electrochromic device is the same as that used in Example 1.

[0142] In this embodiment, the obtained self-healing electrochromic device has a haze of 0.32%, a transmittance of 93.6%, a color-changing response time of 2.1 s, a fading response time of 2 s, and a cycle life of 17,200 cycles. This indicates that the self-healing modification of each layer did not sacrifice the optical and electrochromic properties of the electrochromic device.

[0143] Example 3

[0144] This embodiment provides a self-healing electrochromic device and its preparation method. The self-healing electrochromic device includes a substrate and a first transparent conductive layer, a self-healing electrochromic layer, a self-healing interface transition layer, a self-healing ion conductor layer, a self-healing ion storage layer, a second transparent conductive layer, a self-healing protective layer, and a self-healing encapsulation layer, which are sequentially stacked on the substrate.

[0145] The substrate includes glass with a light transmittance of 96%, a haze of 0.03%, and a thickness of 2 mm;

[0146] Both the first and second transparent conductive layers have a light transmittance of 93%, a haze of 0.06%, and a thickness of 100 nm. Both the first and second transparent conductive layers are ZnO-doped FTO layers, with the ZnO content decreasing from the center of the FTO layer to both sides. Specifically, the Zn content at the center of the FTO layer is 3%, and the Zn content at both sides is 0%.

[0147] The thickness of the self-healing electrochromic layer is 300 nm; the raw materials for preparing the self-healing electrochromic layer include a dynamic covalent polymer and a first metal oxide sol, wherein the dynamic covalent polymer is a polymer containing disulfide bonds, and the first metal oxide sol is WO3 sol; based on the mass of the first metal oxide sol being 100%, the mass percentage of the dynamic covalent polymer is 8%;

[0148] The thickness of the self-healing interface transition layer is 20 nm; the raw materials for preparing the self-healing interface transition layer include dynamic hydrogen-bonded organosiloxane, which includes amino silicone oil and polyethylene glycol siloxane in a mass ratio of 3:1.

[0149] The self-healing ion conductor layer has a transmittance of 94% and a thickness of 6 μm. The self-healing ion conductor layer comprises core-shell self-healing microcapsules (mass ratio 3:10:35:45), modified siloxane, siloxane-modified polyethylene glycol, and lithium salt. The core-shell self-healing microcapsules consist of a core and a shell. The core is a mixture of polyetheramine and epoxy acrylate (mass ratio 1:1), and the shell is SiO2. The core-shell self-healing microcapsules are prepared by the following method: a compound of polyetheramine and epoxy acrylate is dispersed in an aqueous phase as the core material. An emulsifier is added, and the mixture is emulsified at high speed to form a core material emulsion. Then, tetraethyl orthosilicate hydrolysate is added dropwise to adjust the pH of the system to 8.7. In-situ polymerization is carried out at 45°C with stirring for 5 hours to obtain core-shell self-healing microcapsules with an average particle size of 3 μm, a shell thickness of 100 nm, and a transmittance of 96%. The modified siloxane is diethylsiloxane, and the lithium salt is LiTFSI.

[0150] The thickness of the self-healing ion storage layer is 200 nm; the raw materials for preparing the self-healing ion storage layer include a dynamic covalent polymer and a second metal oxide sol, wherein the dynamic covalent polymer is a polymer containing disulfide bonds, and the second metal oxide sol is NiO sol; based on the mass of the second metal oxide sol being 100%, the mass percentage of the dynamic covalent polymer is 5%.

[0151] The self-healing protective layer has a thickness of 80 nm and a surface hardness of 6H. The raw materials for preparing the self-healing protective layer include a wear-resistant material and an organosiloxane in a mass ratio of 7:3. The wear-resistant material is TiO2, and the organosiloxane is PDMS.

[0152] The thickness of the self-healing encapsulation layer is 5 μm; the raw materials for preparing the self-healing encapsulation include epoxy resin containing dynamic covalent bonds, and the epoxy resin containing dynamic covalent bonds is epoxy resin containing disulfide bonds.

[0153] The preparation method of the self-healing electrochromic device is the same as that in Example 2. In order to obtain the self-healing electrochromic device with the above structure, the amount of raw materials and parameters such as process temperature and time can be adjusted.

[0154] Example 4

[0155] This embodiment provides a self-healing electrochromic device and its preparation method. The self-healing electrochromic device includes a substrate and a first transparent conductive layer, a self-healing electrochromic layer, a self-healing interface transition layer, a self-healing ion conductor layer, a self-healing ion storage layer, a second transparent conductive layer, a self-healing protective layer, and a self-healing encapsulation layer, which are sequentially stacked on the substrate.

[0156] The substrate includes glass with a light transmittance of 96%, a haze of 0.03%, and a thickness of 2 mm;

[0157] Both the first and second transparent conductive layers have a light transmittance of 92%, a haze of 0.05%, and a thickness of 200 nm. Both the first and second transparent conductive layers are ZnO-doped FTO layers, with the ZnO content decreasing from the center of the FTO layer to both sides. Specifically, the Zn content at the center of the FTO layer is 2.5%, and the Zn content at both sides is 0%.

[0158] The thickness of the self-healing electrochromic layer is 500 nm; the raw materials for preparing the self-healing electrochromic layer include a dynamic covalent polymer and a first metal oxide sol, wherein the dynamic covalent polymer is a polymer containing disulfide bonds, and the first metal oxide sol is WO3 sol; based on the mass of the first metal oxide sol being 100%, the mass percentage of the dynamic covalent polymer is 5%;

[0159] The thickness of the self-healing interface transition layer is 50 nm; the raw materials for preparing the self-healing interface transition layer include dynamic hydrogen-bonded organosiloxane, which includes amino silicone oil and polyethylene glycol siloxane in a mass ratio of 5:1.

[0160] The self-healing ion conductor layer has a light transmittance of 92% and a thickness of 15 μm. The self-healing ion conductor layer comprises core-shell self-healing microcapsules, modified siloxane, siloxane-modified polyethylene glycol, and lithium salt in a mass ratio of 5:15:40:50. The structure and preparation method of the core-shell self-healing microcapsules are the same as in Example 2. The modified siloxane is a fluorosiloxane, and the lithium salt is LiTFSI.

[0161] The thickness of the self-healing ion storage layer is 400 nm; the raw materials for preparing the self-healing ion storage layer include a dynamic covalent polymer and a second metal oxide sol, wherein the dynamic covalent polymer is a polymer containing disulfide bonds, and the second metal oxide sol is NiO sol; based on the mass of the second metal oxide sol being 100%, the mass percentage of the dynamic covalent polymer is 8%;

[0162] The self-healing protective layer has a thickness of 100 nm and a surface hardness of 6H. The raw materials for preparing the self-healing protective layer include a wear-resistant material and an organosiloxane in a mass ratio of 2:1. The wear-resistant material is SiO2, and the organosiloxane is PDMS.

[0163] The thickness of the self-healing encapsulation layer is 8 μm; the raw materials for preparing the self-healing encapsulation include epoxy resin containing dynamic covalent bonds, and the epoxy resin containing dynamic covalent bonds is epoxy resin containing acylhydrazone bonds.

[0164] The preparation method of the self-healing electrochromic device is the same as that in Example 2. In order to obtain the self-healing electrochromic device with the above structure, the amount of raw materials and parameters such as process temperature and time can be adjusted.

[0165] Example 5

[0166] This embodiment provides a self-healing electrochromic device and its preparation method. Except that the first transparent conductive layer and the second transparent conductive layer are both ITO layers, all other conditions are the same as in Embodiment 2.

[0167] Example 6

[0168] This embodiment provides a self-healing electrochromic device and its preparation method. Except that no modified siloxane is added to the self-healing ion conductor layer, all other conditions are the same as in Example 2.

[0169] Example 7

[0170] This embodiment provides a self-healing electrochromic device and its preparation method. Except that siloxane-modified polyethylene glycol is not added to the self-healing ion conductor layer, all other conditions are the same as in Example 2.

[0171] Example 8

[0172] This embodiment provides a self-healing electrochromic device and its preparation method. Except for the absence of a self-healing protective layer, all other conditions are the same as in Embodiment 2.

[0173] Example 9

[0174] This embodiment provides a self-healing electrochromic device and its preparation method. Except for the absence of a self-healing encapsulation layer, all other conditions are the same as in Embodiment 2.

[0175] Example 10

[0176] This embodiment provides a self-healing electrochromic device and its preparation method. Except for the absence of annealing, all other conditions are the same as in Embodiment 2.

[0177] Comparative Example 1

[0178] This comparative example provides a self-healing electrochromic device and its preparation method. Except that the self-healing electrochromic layer does not contain a dynamically covalent polymer, all other conditions are the same as in Example 2.

[0179] Comparative Example 2

[0180] This comparative example provides a self-healing electrochromic device and its preparation method. Except for the absence of a self-healing interface transition layer, all other conditions are the same as in Example 2.

[0181] Comparative Example 3

[0182] This comparative example provides a self-healing electrochromic device and its preparation method. Except that the self-healing ion conductor layer does not contain core-shell self-healing microcapsules, all other conditions are the same as in Example 2.

[0183] Comparative Example 4

[0184] This comparative example provides a self-healing electrochromic device and its preparation method. Except for the absence of a dynamically covalent polymer in the self-healing ion storage layer, all other conditions are the same as in Example 2.

[0185] The self-healing electrochromic devices obtained in the above embodiments and comparative examples were subjected to performance testing.

[0186] Microcrack repair detection: Microcracks with a width of ≤5μm were prepared on the surface of the electrochromic device using a blade. The crack morphology was observed using an optical microscope. After being placed at room temperature for 24 hours, the cracks were observed again, and the crack healing rate was calculated.

[0187] Performance recovery rate testing: The haze, transmittance, response time, and cycle life of the electrochromic device were tested before and after microcrack repair. The performance recovery rate was calculated as (performance after repair / performance before repair) × 100%.

[0188] The haze was measured using a haze transmittance meter (model WGT-S). Transmittance was measured using a UV-Vis spectrophotometer in the visible light band of 380–780 nm. Response time was tested by applying a 3V voltage jump to the device and measuring the transmittance change at a wavelength of 600 nm; the time it took for the transmittance change to reach 90% was defined as the response time. Cycle life was tested by constant voltage cycling, with a coloring voltage of 3V and a fading voltage of -3V.

[0189] The test results are shown in Table 1.

[0190] Table 1

[0191]

[0192] As shown in Table 1:

[0193] The self-healing electrochromic device and its preparation method provided in Examples 2-4 of this invention construct a triple self-healing system of dynamic covalent bonds + dynamic hydrogen bonds + core-shell self-healing microcapsules, which can actively self-heal at room temperature, recover damage, and extend service life; under preferred conditions, the self-healing rate is ≥95% when the crack width is ≤5μm, and the recovery rate of optical performance and electrochromic performance is ≥96%.

[0194] A comparison of Examples 2 and 5 shows that if the first transparent conductive layer and the second transparent conductive layer are not doped with metal oxides, a large number of microcracks are easily generated due to stress concentration during the thermal cycling process of the conductive layer. Furthermore, the interlayer interface has poor bonding force and lacks a stress buffer structure, making it unable to self-heal the cracks, which leads to a decrease in the self-repair rate of the device.

[0195] A comparison of Examples 2, 6-7, and Comparative Example 3 reveals that if modified siloxane is not added to the self-healing ion conductor layer, the self-healing rate of the device decreases due to the poor hydrophobic stability of the matrix, the easy absorption of moisture by lithium salts leading to precipitation and disruption of the dynamic hydrogen bond crosslinking network, and the loss of continuity of the self-healing matrix. Without the addition of siloxane-modified polyethylene glycol, the compatibility of the functional components deteriorates, the interface between the polymer and the inorganic sol is prone to peeling and cracking, and the uneven distribution of reversible dynamic bonds makes it difficult to complete crack bonding. Furthermore, without the addition of core-shell self-healing microcapsules, the lack of external repair agent after damage means that the repair capacity relying solely on a small number of dynamic bonds in the matrix is ​​limited, and wide cracks cannot be filled, resulting in a decrease in the self-healing rate of the device.

[0196] A comparison of Examples 2 and 8 shows that without a self-healing protective layer, it is not conducive to repairing surface micro-scratches and external impact damage, resulting in a decrease in the self-healing rate of the device.

[0197] A comparison of Examples 2 and 9 shows that without a self-healing encapsulation layer, the micro-gaps at the encapsulation edge cannot be repaired, nor can moisture and oxygen be isolated, resulting in a decrease in both the self-healing rate and environmental stability of the device.

[0198] A comparison of Examples 2 and 10 shows that without annealing, not only is the dynamic bonding system unstable, but the bonding force between the film layers cannot be enhanced, resulting in a decrease in the self-healing rate of the device.

[0199] A comparison of Example 2 and Comparative Examples 1 and 4 shows that if the self-healing electrochromic layer and the self-healing ion storage layer do not contain a dynamic covalent polymer, the molecular chain cross-linking healing of microcracks cannot be achieved, thus failing to restore the ion transport channels and electrochromic active sites, resulting in a decrease in the self-healing rate of the device.

[0200] A comparison of Example 2 and Comparative Example 2 shows that when a self-healing interface transition layer is not provided, interlayer microseparation cannot be repaired, which in turn affects the interlayer bonding force and the continuity of ion transport.

[0201] The present invention has been illustrated with the above embodiments to illustrate its detailed structural features. However, the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions for the components used in the present invention, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A self-healing electrochromic device, characterized in that, The self-healing electrochromic device includes a substrate and a first transparent conductive layer, a self-healing electrochromic layer, a self-healing interface transition layer, a self-healing ion conductor layer, a self-healing ion storage layer, and a second transparent conductive layer, which are sequentially stacked on the substrate.

2. The self-healing electrochromic device according to claim 1, characterized in that, The substrate includes glass; The substrate has a light transmittance of ≥92%, a haze of ≤0.1%, and a thickness of 2mm-3mm; The light transmittance of both the first transparent conductive layer and the second transparent conductive layer is ≥91%, the haze is ≤0.1%, and the thickness is 100nm-200nm. Both the first transparent conductive layer and the second transparent conductive layer are transparent conductive layers with gradient doping of metal oxides, wherein the content of doped metal oxides decreases from the center of the transparent conductive layer to both sides; The metal oxides doped in the transparent conductive layer include any one or a combination of at least two of ZnO, Al2O3, Ga2O3, In2O3, or SnO2. The doped metal content at the center of the transparent conductive layer is 2%-3%, and the doped metal content at both sides is 0%-0.05%.

3. The self-healing electrochromic device according to claim 1, characterized in that, The thickness of the self-healing electrochromic layer is 300nm-500nm; The raw materials for preparing the self-healing electrochromic layer include a dynamically covalently bonded polymer and a first metal oxide sol. The dynamically covalent polymers include polymers containing acylhydrazone bonds and / or polymers containing disulfide bonds; The polymer containing hydrazone bonds is a condensation polymer of acylhydrazine compounds and dialdehydes; The polymer containing disulfide bonds is a condensation polymer of dithiocarboxylic acid compounds and dithiol compounds; The first metal oxide sol includes WO3 sol and / or WO3-TiO2 sol; Based on the mass of the first metal oxide sol being 100%, the mass percentage of the dynamically covalent polymer is 5%-8%; The thickness of the self-healing interface transition layer is 20nm-50nm; The raw materials for preparing the self-healing interface transition layer include dynamic hydrogen-bonded organosiloxanes; The dynamic hydrogen-bonded organosiloxane comprises amino silicone oil and polyethylene glycol siloxane in a mass ratio of (2-5):

1.

4. The self-healing electrochromic device according to claim 1, characterized in that, The self-healing ion conductor layer has a light transmittance of ≥92% and a thickness of 5μm-15μm; The self-healing ion conductor layer comprises the following components: core-shell self-healing microcapsules, modified siloxane, siloxane-modified polyethylene glycol, and lithium salt; The mass ratio of the core-shell self-healing microcapsule, modified siloxane, siloxane-modified polyethylene glycol, and lithium salt is (3-5):(10-15):(30-40):(40-50); The core-shell self-healing microcapsule includes a core and a shell, wherein the core includes a self-healing monomer and the shell includes SiO2; The core-shell self-healing microcapsules were prepared by in-situ polymerization. The self-healing monomer includes polyetheramine and / or epoxy acrylate; The thickness of the outer shell is 50nm-100nm; The core-shell self-healing microcapsules have a light transmittance of ≥95% and an average particle size of 1μm-3μm; The modified siloxanes include fluorosiloxanes and alkylsiloxanes; The lithium salt includes LiTFSI.

5. The self-healing electrochromic device according to claim 1, characterized in that, The thickness of the self-healing ion storage layer is 200nm-400nm; The raw materials for preparing the self-healing ion storage layer include dynamic covalent polymers and second metal oxide sols. The second metal oxide sol includes NiO sol and / or NiO-TiO2 sol; Based on the mass of the second metal oxide sol being 100%, the mass percentage of the dynamic covalent polymer is 5%-8%.

6. The self-healing electrochromic device according to claim 1, characterized in that, The self-healing electrochromic device further includes: a self-healing protective layer and a self-healing encapsulation layer sequentially stacked on the second transparent conductive layer; The thickness of the self-healing protective layer is 80nm-120nm, and the surface hardness is ≥6H. The raw materials for preparing the self-healing protective layer include wear-resistant materials and organosiloxanes in a mass ratio of (2-3):1; The wear-resistant material includes SiO2 and / or TiO2; The organosiloxanes include SiOCH and / or PDMS; The thickness of the self-healing encapsulation layer is 3μm-8μm; The self-healing encapsulation layer is prepared using epoxy resin containing dynamic covalent bonds; The epoxy resin containing dynamic covalent bonds includes epoxy resins containing acylhydrazone bonds and / or epoxy resins containing disulfide bonds.

7. The self-healing electrochromic device according to claim 1, characterized in that, The self-healing electrochromic device has a haze of ≤0.5%, a light transmittance of ≥92%, a color change response time of ≤3s, a fading response time of ≤3s, and a cycle life of ≥15,000 cycles. The self-healing electrochromic device has a self-healing rate of ≥85% when the crack width is ≤5μm.

8. A method for preparing a self-healing electrochromic device as described in any one of claims 1-7, characterized in that, The preparation method includes: A first transparent conductive layer, a self-healing electrochromic layer, a self-healing interface transition layer, a self-healing ion conductor layer, a self-healing ion storage layer, and a second transparent conductive layer are sequentially prepared on a substrate.

9. The preparation method according to claim 8, characterized in that, Both the first transparent conductive layer and the second transparent conductive layer are prepared by magnetron sputtering. The self-healing electrochromic layer, the self-healing interface transition layer, the self-healing ion conductor layer, and the self-healing ion storage layer are all prepared by spin coating. The preparation method further includes: preparing a self-healing protective layer on the second transparent conductive layer, annealing it, and then preparing a self-healing encapsulation layer on the self-healing protective layer; The self-healing protective layer is prepared by electron beam evaporation. The annealing temperature is 80℃-120℃, and the time is 40min-80min; The self-healing encapsulation layer is prepared using a blade coating method.

10. An application of the self-healing electrochromic device as described in any one of claims 1-7, characterized in that, The self-healing electrochromic device is used in automotive rearview mirrors, smart windows, or display devices.

Citation Information

Patent Citations

  • Epoxy resin containing dynamic covalent bonds and synthesis method thereof, and preparation method of self-repairing epoxy structure adhesive

    CN119081067A

  • Novel epoxy resin as well as preparation method and application thereof

    CN120040719A